Evaluation of Taste Disturbance in Pre and Post Mastoid Surgery Patients - Manandhar, Sriti; Chettri, ST; Kandel, DR (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Mastoid surgery is one of the commonest surgeries in Otolaryngology & Head & Neck department. Surgeons are less aware of preserving chorda tympani nerve (CT). Injury to the chord tympani nerve is common in middle ear surgery as the course of CT runs between ossicles and close to tympanic membrane. It makes the surgeon difficult to preserve it during the surgery. The study was done to observe frequency of taste disturbances (TD) in all patients undergoing mastoid surgery and to correlate between intra operative status of CT and type of intra operative status of CT injury with postoperative taste disturbances. Methods: A prospective analytical study was conducted in patients who underwent mastoid surgery. The intra operative status of CT was studied, different forms of injury to the nerve were noticed and its impact on taste disturbances was assessed subjectively with questionnaire. The patients with taste disturbances were followed till twelve weeks. Result: None of the patients had taste disturbances prior to surgery. Out of 65 patients, only 15 patients became symptomatic in second postoperative day and the taste disturbances were in the form of altered taste (26.66%), dry mouth (26.66%) and numbness (46.66%). Symptoms like altered taste and numbness were present till the eighth week of surgery and disappeared by the twelfth week except one patient in whom numbness persisted till twelfth week. The symptoms did not correlate with the intra operative status of CT. The symptoms disappeared with duration of operation and it was significant. Conclusion: None of the patients voluntarily complained regarding taste disturbances until they were specifically asked. Only 15 patients had taste disturbances; 7 had numbness, 4 dryness of mouth and 4altered taste. The taste disturbances did not correlate with the type of intra operative status of CT. CT was not identified in 9 patients and only 3 (33.3%) became symptomatic and CT was cut with micro scissors in 26 patients but only 4 (15.38%) patients were symptomatic.